Barriers to Optimal Social Support in the Postpartum Period. Issue 4 (19th June 2014) - Barkin, Jennifer L.; Bloch, Joan R.; Hawkins, Kristina C.; Thomas, Tiffany Stanfill
ABSTRACT Objective To examine the specific barriers to mothers' realization of social support during the first‐year postpartum. Design A qualitative approach in which social support data were analyzed thematically. Setting An urban medical center in Pittsburgh, Pennsylvania. Participants Thirty‐one women who had given birth in the year prior to study enrollment were recruited through posted flyers at multiple community sites. Methods Data were collected during three focus groups. The data that related to social support were extracted from a larger qualitative data set and analyzed separately for prominent social support inhibitors. Results Major themes that emerged were availability of trustworthy child care, cost of child care, demands of infant care, changing priorities, a transient population, and availability of family. Conclusions Emergent barriers to social support such as the demands of infant care and changing priorities are likely challenges for women regardless of socioeconomic status. However, the volume of text related to availability (proximity) of family, availability of trustworthy child care, and the consequences of a transient lifestyle may be attributed to the composition of the study sample.